CALIDAD DE ATENCION AL CLIENTE EN EL REGISTRO DE LA PROPIEDAD DEL GAD BABAHOYO - Figueroa Alvarado, Edwin Nicasio (2019)
The Decentralized Autonomous Government of the City of Babahoyo within the various activities and processes that develop has the property registration department that aims to register, annotate and cancel the acts and contracts relating to the domain and other real rights over immovable property and identifiable furniture; the registration of the property when forming part of the Municipal GAD of Babahoyo is a Public entity, currently they provide their services in the offices located in the main building of the Municipality of Babahoyo in the streets General Barona and Calderón.